TANTANGAN PENYUSUNAN ADMINISTRASI PEMBELAJARAN DI ERA KURIKULUM MERDEKA DI SDN 1 BABAKAN KABUPATEN PURWAKARTA - Ade Tutty Rokhayati Rosa; Andris Hadiansyah; Asep Sapari; Dewi Rosmalasari; Wily Aulia Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Independent Curriculum in Indonesia represents an educational transformation aimed at providing teachers with greater flexibility in designing adaptive, contextual, and student-centered learning. This curriculum emphasizes competency-based learning outcomes, character strengthening through the Pancasila Student Profile, and simplified yet deeper learning materials. However, this paradigm shift also brings new challenges, particularly in learning administration that must be prepared by teachers in schools. At SDN 1 Babakan Purwakarta Regency, the implementation of the Independent Curriculum reveals several difficulties in preparing learning administration, especially in adapting administrative formats, understanding curriculum concepts, and utilizing digital learning technologies. This study aims to analyze the challenges of preparing learning administration in the Independent Curriculum era. The focus includes teachers’ difficulties in developing teaching modules, learning objective pathways, and project-based learning integration. This research uses a qualitative approach with data collection techniques such as interviews, observations, and documentation. The informants consist of teachers and school stakeholders directly involved in the learning process. The findings indicate that teachers still face obstacles in understanding the administrative structure of the Independent Curriculum, limited training opportunities, and adaptation to new learning systems. In addition, increased administrative workload also becomes a challenge in achieving effective learning implementation. Therefore, continuous training and mentoring are needed to ensure the optimal implementation of the Independent Curriculum in schools.